2021
DOI: 10.1002/aenm.202101915
|View full text |Cite
|
Sign up to set email alerts
|

Superionic Fluorinated Halide Solid Electrolytes for Highly Stable Li‐Metal in All‐Solid‐State Li Batteries

Abstract: The halide solid‐state electrolytes (SSEs) have received significant attention due to their high ionic conductivity and desirable compatibility with cathode materials. However, the reduction potential of the halide is still >0.6 V (versus Li/Li+). Reduction stability is still one of the challenges that need to be addressed. The fluorides have a wide electrochemical stability window due to the large electronegativity of F–. In contrast, Li3YBr6 (LYB) bromides have a narrower electrochemical window, although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 34 publications
2
78
1
Order By: Relevance
“…Note that although we noticed that certain specific halide doping procedures for the Li–argyrodite electrolyte were reported recently, , such a quantitative design through precise composition control within our two-parameter phase space and the experimental implementation through the core–shell strategy and related synthesis are proposed and demonstrated for the first time, representing a unique fundamental understanding with significant practical values. More importantly, our approach can be further applied to the design of broad types of electrolyte materials with similar dynamic stabilities to various interfaces, including sulfides, halides, oxides, , ceramics, glasses, and polymers and their composites.…”
Section: Discussionmentioning
confidence: 99%
“…Note that although we noticed that certain specific halide doping procedures for the Li–argyrodite electrolyte were reported recently, , such a quantitative design through precise composition control within our two-parameter phase space and the experimental implementation through the core–shell strategy and related synthesis are proposed and demonstrated for the first time, representing a unique fundamental understanding with significant practical values. More importantly, our approach can be further applied to the design of broad types of electrolyte materials with similar dynamic stabilities to various interfaces, including sulfides, halides, oxides, , ceramics, glasses, and polymers and their composites.…”
Section: Discussionmentioning
confidence: 99%
“…The LSV results for Li 3 YBr 5.7 F 0.3 compared to Li 3 YBr 6 showed that the onset voltage for the reduction was shifted in the negative direction and the overall reduction currents were decreased (Figure d). In addition, the XPS depth profiling results revealed the formation of LiF at the Li metal interfaces, which helped the passivation of the interfaces . For Li/SE/Li symmetric cells using Li 3 YBr 6 , a high overpotential of ∼0.25 V occurred initially and continued to increase after 300 h. In contrast, a much lower overpotential was maintained for more than 1000 h for the F-substituted sample (Figure e).…”
Section: Halide Ses For All-solid-state Batteriesmentioning
confidence: 93%
“…9 Indeed, several literature reports on halide SEs have adopted the dual electrolyte configuration for ASSB systems. 22,49,51,72,126,127 ■ INDUSTRIAL PERSPECTIVE OF HALIDE SEs Air/Moisture Stability. Better chemical oxidation stability is a key positive feature of halide SEs compared to sulfide SEs.…”
mentioning
confidence: 99%
“…This is remarkably different from most of the previous studies employing elemental doping to stabilize the sulfide solid electrolytes. [61,62]…”
Section: (3 Of 10)mentioning
confidence: 99%